Samsung’s CSR in Solving Educational Issues in India - Nur Izzah Anisah Ismail (Jurnal Hubungan Internasional, 2022)
This paper discusses how corporate social responsibility could help in assisting states with global issues. The globalization which is experienced by every part of the world has created new and more complex issues. These issues sometimes cannot be solved by the state solely, demanding a global governance with the hope to cope with the issues. The existence of multinational corporations (MNC) as a new rising actor, through their corporate social responsibility (CSR) is hoping to be responsible to the society they operate. The writer argues that through the Public-Private Partnership, the CSR by MNC can help the state in solving the global issues faced by them. One of the global issues that needs the attention of the community is educational issues, especially in developing states. To strengthen the writer’s argument, this paper will raise a case study on Samsung’s CSR and their impacts on India educational issues. India is one of the states who is battling with the educational issues, and Samsung as one of the biggest MNC in India is actively assisting the government regarding the issues. The success of these CSR can be seen through the response of the Indian local government.